A Novel Method for Analyzing the Kinetics of Convective/IR Bread Drying (CIRD) with Sensor Technology - Marko Petković; Alexander Lukyanov; Igor Đurović; Nemanja Miletić (Applied Sciences)
This study explores the combined use of convective and infrared drying (CIRD) for bread slices, utilizing advanced MEMS sensors to monitor temperature, moisture, and drying rates in real time, optimizing efficiency, and energy use. The dehydration kinetics of 1 cm thick bread slices under a controlled CIRD method was used. This analyzes drying rate (water loss speed, WLS) and energy efficiency (EE) using sensor technology. IR drying used 150 W lamps at 7 cm and 15 cm, while convective drying involved 60 °C hot air at 3 m/s. Sensor data aligned with gravimetric measurements. The most energy-efficient model used a 150 W IR lamp at 7 cm (0.645 kWh, 21.572 kWh/kg water removed) but had the longest drying time (220 min at 15 cm). The least efficient model used a 250 W IR lamp at 15 cm (EE = 32.734 kWh/kg). These results of CIRD in bread drying are statistically significant and can be applied to industrial bakery drying processes, helping manufacturers to reduce energy costs, and adopt sensor-driven process control for enhanced sustainability. The CIRD model, which uses a 150 W IR lamp placed 15 cm above the bread slices being dried, represents the most effective optimization strategy.